A Tale of Two States: Pluripotency Regulation of Telomeres - Novo, Clara Lopes (Frontiers in Cell and Developmental Biology, 2021)
Inside the nucleus, chromatin is organized and functionally maintained as a complex three-dimensional network of structures with different accessibility such as compartments, membraneless bodies and lamina-associated domains. Chromatin is epigenetic and transcriptionally regulated by an intricate and dynamic interplay of molecular processes to ensure genome stability. Recently, liquid–liquid phase-separation (LLPS), a process that involves the spontaneous organization of a solution into two phases, has been proposed as a mechanism for a timely coordination of several cellular processes, including replication, transcription and DNA repair. Telomeres, the repetitive structures at the end of chromosomes, are epigenetically maintained in a repressed heterochromatic state that prevents their recognition as double-strand breaks (DSB), avoiding DNA damage repair and ensuring cell proliferation. In pluripotent embryonic stem cells, telomeres adopt a non-canonical relaxed epigenetic state, characterized by a low density of histone methylation and increased telomere non-coding transcripts (TERRA). Intriguingly, this telomere non-canonical conformation is usually associated with chromosome instability and aneuploidy in somatic cells, raising the question of how genome stability is maintained in a pluripotent background. Here, we will explore how emerging technological and conceptual developments in 3D genome architecture can provide novel mechanistic perspectives for the pluripotent epigenetic paradox at telomeres. In particular, as RNA drives the formation of LLPS, we will consider how pluripotency-associated high levels of TERRA could drive and coordinate phase-separation of several nuclear processes to ensure genome stability. These conceptual advances will provide a better understanding of telomere regulation and genome stability within the highly dynamic pluripotent background.